Influence of plant growth regulators on yield and quality of Karonda (Carissa carandas L.) (Indian Journal of Arid Horticulture, 2017)
An experiment was conducted on 6 year-old- plants of karonda at the Horticultural Research Station of BidhanChandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal to know the effect of different growth regulators on fruityield and physico-chemical composition of fruits. There were five treatments viz., NAA at 20, 40 ppm; GA at 20 and 40 ppmand control (water spray) which were sprayed two times i.e., at 50% flowering stage and 21 days after 1st spray. Theexperiment was conducted following the randomized block design having four replications. The study clearly indicated thatplant growth regulators were effective at different concentration in increasing fruit yield and physico-chemical characteristicsof fruits. Application of NAA at 20 ppm resulted in maximum fruit set (93.62% ), fruit retention (83.0%) and fruit yield ( 4.07kg/plant). The treatment also increased fruit weight and pulp content while GA at 20 ppm was found to be the best forincreasing TSS (8.87°B), total sugars (6.05%), ascorbic acid (34.00 mg/100 g) and anthocyanin (3.87 mg/100 g pulp) contentsfollowed by NAA 20 ppm. Considering the over all performance and lower market price, the NAA at 20 ppm isrecommended for higher production of quality karonda fruits in new alluvial zone of West Bengal.
Keywords: Fruit quality; fruit yield; karonda; plant growth regulators